Effect of substituents and chain length in amino-1, 4-naphthoquinones on glutathione-S-transferase inhibition: molecular docking and electrochemical perspectives: a structure–activity study. (2nd November 2022) - Faúndes, Judith; Muñoz-Osses, Michelle; Morales, Pilar; Tasca, Federico; Loyola, César Zúñiga; Faúndez, Mario; Mascayano, Carolina; Ibacache, Juana A.
Abstract : The highlights of structure–activity relationship in GST inhibition. Abstract : In this study, new homodimers and monoamination products based on the pharmacophore amino-1, 4-naphthoquinone were synthesized. To perform a structure–activity study, three precursor quinones (2, 3-dichloro-1, 4-naphthoquinone, 1, 4-naphthoquinone, and 2-hydroxy-1, 4-naphthoquinone) and four diamines (4, 4′-diaminodiphenylmethane, 4, 4′-ethylenedianiline, ethylenediamine and 1, 3-diaminopropane) were used. The reactions of the compounds were accomplished in the presence or the absence of Lewis acid as a catalyst. The new derivatives were evaluated as potential inhibitors of the enzyme glutathione-S-transferase (GST) by conjugating reduced glutathione (GSH) with the substrate 1-chloro-2, 4-dinitrobenzene (CDNB). The study of the GST activity showed a clear structure–activity relationship in which the chlorinated compound 8 was the best inhibitor, with inhibition percentage values of 57%, being in the inhibition range as other GST inhibitors such as hexachlorophene and ethacrynic acid. These experimental results are consistent with molecular docking studies which show that compound 8 binds to the enzyme close to the catalytic site (G-site) and the chlorine group shows up to be essential for the stability of the ligand. Additionally, from the in silico exploration, a directly proportional trend between lipophilicity and enzyme affinity was noted, correlating with the experimental results of GST activity where the chlorine atom contributes positively to it. Finally, the electrochemical characterization provided another significant insight: the compounds with higher formal potential values ( E 0 ) had the electron-withdrawing group chlorine being the most active against GST.